Measles， rubella， and mumps antibody seroprevalence among the children aged 18 years and younger in Karamay City， Xinjiang Uygur Autonomous Region - WU Meili; LI Xia; ZUO Ling; RONG Liping; WANG Jing; WANG Feng (Shanghai yufang yixue)
ObjectiveTo understand the measles, rubella, and mumps antibody seroprevalence among the children aged 18 years and younger in Karamay City, and to evaluate the effectiveness of vaccination.MethodsA stratified whole cluster random sampling method was used to investigate the antibody seroprevalence of measles, rubella, and mumps among the healthy children aged 18 years and younger in Karamay City, and to further analyze the positive antibody rates and the geometric mean concentration (GMC) of antibodies.ResultsA total of 620 people were investigated, and the positive rates of IgG to measles, rubella, and mumps were 72.74%,62.26%, and 86.45%, respectively, with a GMC of 308.94 mIU·mL-1, 21.81 mIU·mL-1, and 249.10 U·mL-1. There were statistically significant differences in the positive rates of antibodies to measles, rubella, and mumps among different age groups (χ2measles=76.707, P<0.001; χ2rubella=60.804, P<0.001; χ2mumps=35.407, P<0.001). The differences in positive rates were statistically significant among individuals with different intervals from the time of their last dose vaccination (χ2measles=60.533, P<0.001; χ2rubella=46.331, P<0.001; χ2mumps=22.825, P<0.001).ConclusionThe antibody levels of measles, rubella and mumps among the people aged 18 years and younger in Karamay City are found to be low. Two doses of measles-mumps-rubella (MMR) vaccine should be given to children born before 2020, and if necessary, supplementary immunization with MMR vaccine should be carried out before they are enrolled in nursery and kindergarten. Additionally, regular population-based antibody surveillance should be conducted to promptly identify the people with weak immunity, which is conducive to effectively reducing and controlling the epidemic situation of measles, rubella and mumps in schools.